Case Reports Acute Mesenteric Ischemia Due To Sma Thrombosis- A Case Reports (Indian Journal of Applied-Basic Medical Sciences, 2022)
INTRODUCTION:Acute mesenteric ischemia usually presents as abdominal pain that is out of proportion in relation to tenderness; persistent vomiting, bloody diarrhea and shock. Sloughing of intestinal mucosa takes 3 hours while infarction of entire bowel thickness occurs in 6 hours. [1]- [3] CECT abdomen with mesenteric angiography is investigation of choice. If patient has presented after 24-48 hours, gangrene might have already occurred, resection and anastomosis is done majority of cases with removal of vascular block under Doppler guidance or Injection of papaverine. Minimum bowel length required to be retained is 1.2 meters, otherwise the patient will have high mortality due to short bowel syndrome. [4]- [7] AIMS AND OBJECTIVES 1 ] To compare the surgical findings in various case scenarios having different presentations, patient factors and time of presentations with SMA thrombosis 2 ]To compare outcomes of surgical intervention in different case scenarios CONCLUSION:SMA thrombosis was seen in non-covid time as well. Hypercoagulable state which corresponds to raised d-dimer and FDP, the cases of mesenteric ischemia due to SMA thrombosis are seen more commonly in covid-19 era. This series draws to attention that timely diagnosis and appropriate surgery with resection and proper follow up with anti-coagulant the morbidity and mortality is averted. Acute mesenteric ischemia is commonly due to emboli (45-50%) rather than thrombosis (20-25%). Non occlusive disease (5-15%) can be due to various causes e.g., pancreatitis, sepsis, heart failure, etc. Early diagnosis is the key to successful management. Aggressive resuscitation, early revascularization with vascular intervention and exploratory laparotomy is done if evidence of peritonitis is present.[8]-[9] Postoperative fluid management due to short bowel syndrome and appropriate antibiotic coverage is necessary to revive the patient. Long term TPN support for patients with short bowel patients is necessary. They are candidates for intestinal transplantation if survived.
Keywords: acute; Mesenteric Arteries; Thrombosis- A Case Reports